Converting physical spaces into learning spaces: Integrating universal design and universal design for learning - Khurana, Aashna (Frontiers in Education, 2022)
The term “Universal Design for Learning (UDL)” is derived from “Universal Design,” which is commonly used in the field of architecture, and focuses on proactive designing of the infrastructure that is accessible to all the users, regardless of their age, sex, abilities, etc. When the universal design approach is implemented in education, it focuses on making the curriculum, instruction, materials, and assessments accessible for all the learners, but does not mention anything about the classroom and school infrastructure. This raises a question: is the UDL framework forgetting the origin of universal design by not recognizing the importance of physical spaces or school infrastructure, where all the learning takes place? A way to approach this question is to think of school infrastructure as a learning resource that provides enriching learning experiences to the learners, and not merely a brick-and-mortar structure that houses instruction. The school building comprises various physical spaces such as classrooms, corridors, playgrounds, staircases, etc. that can be transformed into learning spaces to promote subconscious learning in learners and ensure a school-wide implementation of UDL. Transforming the school environment would ensure learners an equitable, inclusive, and accessible environments that address learner variability, and reduce barriers to their learning. This involves a focus on various components, namely, transforming physical spaces (universal design) into learning spaces (universal design for learning), identifying different elements in each learning space to maximize their learning value, and general accessibility of the school infrastructure. The chapter aims to provide a framework to design inclusive learning spaces by deriving insights from the work of various groups of architects in India, Ireland, and the United States that have explored the relationship between physical spaces and UDL.